Identifikasi Permasalahan Pembelajaran Mahasiswa Tunanetra Pada Mata Kuliah Sintaksis Bahasa Inggris: Studi Kasus di Universitas Dian Nuswantoro - Sunardi Sunardi; Raden Arief Nugroho; Budi Harjo (INKLUSI, 2014)
This study focuses on identifying the problems faced by visually impaired students in teaching-learning  process of English syntax course at Faculty of Humanities, Dian Nuswantoro University in 2014. English syntax, as one of the subjects studied in the English study program, is considered as a challenging subject for visually impaired students as it involves visual perception, such as graphics and images. This research was a descriptive qualitative one. The researchers collected the data by using an in-depth interview. This involved 2 visually impaired students who experienced the learning process of English syntax and 3 lecturers of Dian Nuswantoro University. The discussion was limited on the issues around the needs for creating an accessible learning media and kinds of difficulties faced by the visually impaired students. From the in-depth interview, there are three major findings that are highlighted: a) the needs to overcome all inaccessible English syntax learning materials; b) general difficulties faced by visually impaired students in English syntax subject; c) technical difficulties in drawing tree structure diagrams. Then, these highlighted problems and findings are used as to formulate the recommendations of this study.